Numerical Study on 3-D Laser Forming by Discrete Section Circle Line Heating - Venkadeshwaran, K.; Misra, D. (Advanced Aspects of Engineering Research Vol. 1, 2021)
Laser forming of sheet metal is the bending process, induced by thermal stress, which is produced in the sheet by laser irradiation. Laser forming of complex shapes requires the study of the effect of various irradiation paths. In this paper the deformation of a circular plate, subjected to a circular irradiation path, is studied through a sequentially coupled thermo-mechanical elasto-plastic simulation by finite element method. The quality of laser bending in terms of waviness parameters, e.g., waviness average, Ra, RMS value, Rq, etc. are reported in detail, with respect to number of sections and number of passes of heating, as well as, shifting of the starting point for irradiation. It is observed that discrete section heating in symmetry with shifting in starting point of irradiation in subsequent passes reduces the undesired waviness, which is caused, otherwise, due to continuous circular heating. The results of finite element simulations presented in this chapter principally showed the possibility for a further increased knowledge of the mechanisms in 3D-laser forming.